N4 RNA Polymerase II, a Heterodimeric RNA Polymerase with Homology to the Single-Subunit Family of RNA Polymerases - Willis, S. H. (American Society for Microbiology, 2002)
Bacteriophage N4 middle genes are transcribed by a phage-coded, heterodimeric, rifampin-resistant RNA polymerase, N4 RNA polymerase II (N4 RNAPII). Sequencing and transcriptional analysis revealed that the genes encoding the two subunits comprising N4 RNAPII are translated from a common transcript initiating at the N4 early promoter Pe3. These genes code for proteins of 269 and 404 amino acid residues with sequence similarity to the single-subunit, phage-like RNA polymerases. The genes encoding the N4 RNAPII subunits, as well as a synthetic construct encoding a fusion polypeptide, have been cloned and expressed. Both the individually expressed subunits and the fusion polypeptide reconstitute functional enzymes in vivo and in vitro.